(5x - 4)(3x + 5)
Chat with our AI personalities
(5x - 4)(3x + 5)
12x+x = 13x
15x2-56 = 88+6x2 15x2-6x2-56-88 = 0 9x2-144 = 0 Divide all terms by 9:- x2-16 = 0 (x-4)(x+4) = 0 x = 4 or x = -4
(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2
Provided that x- 2 is not zero: 2x3 + x2 - 13x + 6 = 2x3 - 4x2 + 5x2 - 10x - 3x + 6 = 2x2*(x - 2) + 5x*(x - 2) - 3*(x - 2) = (x - 2)*(2x2 + 5x - 3) Therefore, (2x3 + x2 - 13x + 6)/(x - 2) = (x - 2)*(2x2 + 5x - 3)/(x - 2) = 2x2 + 5x - 3 If x = 2 so that x - 2 = 0, then the expression is not defined.